2008
DOI: 10.1097/hjh.0b013e3282f2b93c
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine increases chemoreflex sensitivity to hypoxia in non-smokers

Abstract: This is the first study to demonstrate that nicotine increases peripheral chemoreflex sensitivity to large reductions in arterial oxygen content in healthy non-smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 59 publications
0
15
2
Order By: Relevance
“…The oscillations result from high ventilatory sensitivity to carbon dioxide (CO 2 ) and hypoxia in the presence of narrowed CO 2 reserve and induce frequent arousals from sleep. Nicotine, NO and carbon monoxide (CO) influence the regulation of breathing 17 18. We speculate that smokers slept better because of less breathing instability through higher nicotine and CO, and lower NO levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oscillations result from high ventilatory sensitivity to carbon dioxide (CO 2 ) and hypoxia in the presence of narrowed CO 2 reserve and induce frequent arousals from sleep. Nicotine, NO and carbon monoxide (CO) influence the regulation of breathing 17 18. We speculate that smokers slept better because of less breathing instability through higher nicotine and CO, and lower NO levels.…”
Section: Discussionmentioning
confidence: 99%
“…Chemoreceptor function is modulated by NO and CO 17. Nicotine increases peripheral chemoreflex sensitivity to reductions in arterial oxygen content in non-smokers but not in smokers 18. In people who live at altitude all their lives, a decrease in ventilation may eventually develop 23.…”
Section: Discussionmentioning
confidence: 99%
“…This could also be due to more localized effects of baroreflexmediated sympathetic vasoconstriction of arterioles supplying the carotid and aortic bodies. Reduced local blood flow might result in a neural discharge similar to that evoked by asphyxia, anoxemia (2), or nicotine and cyanide (1,7,19). Indeed, McCloskey (20) showed that increased impulse traffic of the carotid sinus nerve is easily elicited by hypotension-induced reductions in carotid body blood flow.…”
Section: Increased Pcs and Set Point In Potsmentioning
confidence: 95%
“…One earlier study by Kawakami et al [26] in smokers (SM) and their non-smoking (NSM) homozygote twins failed to demonstrate a smoking-related HVR attenuation after a 3-h-abstinence which is insufficient to eliminate nicotine with an in-vivo half-life of 2 h, as already speculated by these authors themselves. In fact, subsequent studies, including one from the same group, have shown an acute HVR-increase through smoking in both, SM and NSM probably mediated through carotid chemoreceptors [27–30] which might have masked a possible HVR attenuation in the elegant study by Kawakami et al [26] in twins.…”
Section: Introductionmentioning
confidence: 99%